INVENTARISASI DAN KARAKTERISASI PLASMA NUTFAH PERTANAMAN UBI JALAR (Ipomoea batatas L.) DI PULAU LOMBOK - Sumarjan Sumarjan; Lestari Ujianto; Agung Bagus Darma (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Lombok Island as an area that still has a high level of food insecurity is deemed necessary to develop tuber crops such as sweet potatoes, this is to support the diversity of existing food sources. This study aims to determine: 1) sweet potato germplasm cultivated on Lombok Island; and 2) the characteristics of sweet potato germplasm on Lombok Island. This research uses a descriptive method. Inventarization is carried out by the exploration method, and using cluster analysis which is then displayed in the form of a phenogram. The results showed: 1) obtained 17 accessions of sweet potato plants spread in 4 districts of Lombok Island; 2) the accessions found consisted of accessions of Sweet Potato KLU, Honey KLU, Purple 04 KLU, Orange Lobar, White Lobar, Purple 01 Lobar, Purple 02 Lobar, Purple 03 Lobar, Ornamental Attic, Attic Yellow, Attic White, Purple 01 Attic, Purple 02 Attic, Honey Lotim, Sokan Lotim, Purple 05 Lotim, and Purple 06 Lotim; 3) the cause of the differences in the characteristics of all observed accessions is genetic factors that are supported by different growing environmental conditions. In the accession of Sweet Potato Beduk KLU and Sokan Lotim are local varieties of sweet potato from Lombok Island, so it needs to be developed to maintain local superior sweet potato varieties from Lombok Island.